Flow analysis of an engine nacelle in crosswind : inlet vortices and their interactions - Luis Gustavo Trapp (2012)
Aircraft engines and nacelles operating under crosswind present some design challenges. One of the phenomenon that requires a better comprehension is the vortex that forms between the ground and the engine inlet because this vortex can suck debris into the engine and also affect the engine operability. This work establishes procedures and criteria for using CFD for evaluating crosswind conditions that affect aeronautical engines. A new correlation, the streamtube diameter ratio (SDR), is proposed to predict the inlet vortex appearance and intensity. The different inlet vortices are described in detail, among them the trailing vortex, composed of trailed and ingested parts; and a new vortex, called the feeding vortex. Additionally the interaction between the different vortices is shown, highlighting the importance the nacelle walls have in the strengthening of these vortices. In this process a new analysis methodology is shown, in which the wall boundary conditions used in the CFD analysis are selectively changed between slipping and non-slipping walls, allowing to discover correlations between the different vorticity sources and the vortices'; intensities.